HRTEM evaluation of primary soot particles originated in a small-bore biofuel compression-ignition engine. (August 2019) - Hwang, Joonsik; Hirner, Felix Sebastian; Bae, Choongsik; Patel, Chetankumar; Gupta, Tarun; Agarwal, Avinash Kumar
Highlights: Biodiesel fuels showed higher particulate matter emissions than diesel fuel. High viscosity biodiesel fuels showed unburned hydrocarbon layer in primary particles. WCO biodiesel showed the smallest primary particle diameter among the tested fuels. Biodiesel fuels had larger fringe spacing compared to that of diesel. Abstract: Nanostructure of soot particles from a small-bore compression-ignition engine was investigated by high-resolution transmission electron microscopy (HRTEM). Four test fuels namely conventional diesel, waste cooking oil (WCO) biodiesel, Jatropha biodiesel, and Karanja biodiesel were studied. Lacey carbon TEM grids were utilized to capture soot particles from engine exhaust gas. An in-house image processing algorithm was developed to measure primary particle diameter, fringe length, fringe tortuosity, and fringe spacing. The HRTEM image revealed the presence of thicker absorbed hydrocarbon layers surrounding biodiesel soot primary particles than those of diesel soot. The primary particle size of WCO biodiesel was smaller than diesel, on the other hand, Jatropha biodiesel and Karanja biodiesel showed slightly larger particles. In terms of nano-structure analysis, WCO biodiesel and Jatropha biodiesel particles exhibited shorter fringe length than diesel, while the Karanja biodiesel particles showed the longest fringe length of 0.91 nm. Fringe tortuosity of biodiesels was smaller than diesel because of relatively lower portion of core area, where highly curved fringes existed. The soot particles from biodiesels exhibited larger fringe spacing than diesel, especially the Karanja biodiesel showed the longest fringe spacing of 0.67 nm compared to 0.55 nm in case of diesel.